Workshop on Implementing the Merdeka Curriculum in Indonesian Language Instruction for Elementary School Teachers in Karangpandan, Indonesia - Anindyarini, Atikah; Sumarwati, Sumarwati; Suryanto, Edy; Slamet, Slamet; Hidayah, Laila Fitri Nur; Alfien, Moh. Fajrul; Mulyani, Rahmatika (Universitas Negeri Semarang, 2025)
In implementing the Independent Curriculum, not all teachers understand the principles of developing teaching modules. This community service program aims to provide training and mentoring to elementary school teachers in Karangpandan District, Karanganyar Regency, in planning and implementing Indonesian language learning. The activity partner is the Karanganyar Regency Education and Culture Office. Thirty teachers from Karangpandan District participated. The methods used were expository, sharing ideas, modeling, and mentoring. This community service program uses a participatory approach, actively involving participants at all stages of the activity. The method used in this activity is divided into three stages: preparation, implementation, and evaluation and reporting. The training consisted of material presentations accompanied by examples through workshops so that teachers had the opportunity to practice. Mentoring was carried out after teachers practiced creating learning tools (teaching modules), then a review of the teaching modules was conducted by assessing the quality of the Indonesian language lesson assessment tools. The results of the community service activity are as follows. First, all teacher participants were 100 percent present at the workshop. Second, of the 30 active workshop teachers, 28 teachers compiled Indonesian language teaching modules for grade 4 and were willing to revise them. Third, 25 teachers were able to compile teaching modules well.